An Analysis of the English Teachers’ Ability in Creating Online Teaching Media at Surabaya and Sidoarjo Islamic Senior High Schools - Safriyani, Rizka (JET ADI BUANA, 2016)
As an English teacher, teacher must be able to develop agood teaching media. Traditional textbooks, while useful, areinsufficient to address many questions. As a result, teachers try tolook for another resources, social networks, and the web foranswers to their questions. This study focuses on the teachers’ability in creating online teaching media at Surabaya and SidoarjoSenior High School. This study also portrays the challenges andthe opportunity of the online teaching media usage. It also coversthe information about language preferably used by teacher in theonline teaching media usage. Nine teachers are chosen fromSurabaya and Sidoarjo as the subject of the study. Quantitative andQualitative approach is used as the design of the research.Interview and documentation are used to collect the data. Next, thedata are analyzed by using Likert Scale followed by triangulation.The result shows that teachers’ ability in creating teaching media isgood. The challenges of online teaching media usage are schoolfacilities, time management and school regulation. The opportunityof online teaching media usage are active learner, monitoring roleand active teachers. The language preferably used by teachers ontheir online teaching media are English Indonesia, English andEnglish Arabic.